Youth theatre and community empowerment in Ghana - Nyatuame, Promise Nyatepeh (Amfiteater (Ljubljana), 2021)
As contemporary theatre and new production models are now being evaluated with more regard to community empowerment, the importance of proper tools for evaluation of the process has increased. The article explored the community youth theatre practices of the Community Youth Cultural Centre (CYCC) of the National Commission on Culture (NCC) in Ghana. We examined the role of the youth theatre at CYCC in the light of community empowerment. Using the qualitative case study design, six artists with a minimum of five years and a maximum of thirty years of work experience with the CYCC were interviewed. Performance activities and documents of the CYCC were also observed and analysed. The findings revealed four themes: Objectives of the centre; Youth theatre practices; Abibigoro/puppetry theatre models; and non-formal and cultural education. It was found that staff and artists at the CYCC employed diverse theatrical modes to facilitate community empowerment processes. The study recommends that cultural and creative centres in Ghana should harness the potentials of the community youth theatre, develop community-specific and context-driven performance models to support artistic-aesthetic-cultural and non-formal education processes to enhance our collective strive for community empowerment in Ghana.
Keywords: community; empowerment; gledališče v Gani; ljudje; mladinsko gledališče; opolnomočenje; people; skupnost; theatre in Gana; youth theatre